Penerapan Teori Akad pada Perbankan Syariah - Rauf, Abdur (Faculty of Shariah and Law, 2012)
This article discuss about theory concept of transaction in Islamic banking products. In collecting and distributing funds, Islamic banking used variaety of transactions, such as deposit transactions, (wadiah yad amanah, wadiah yad dhamanah), transactionn for results (mudharabah, musyarakah), buying and selling (murabahah, salam, istishna), lease transaction (ijarah, ijarah wa iqtina, or ijarah muntahiya bi al-tamlik), loan transactions (qardh), and transaction with other patterns (wakalah, kafalah, hiwalah, rahn). Murabahah and salam transactions are used for funding. Meanwhile, ijarah and wakalah are used in loan transactions that implemented in a bank guaranteeDOI: 10.15408/aiq.v4i1.2081